Yenidoğan sağlığı postpartum depresyon ve emzirme dav - Suyer, Sema (My University, 2011)
1. ÖZET Araştırma, yenidoğan sağlığının postpartum dönemdeki kadında postpartum depresyon ve emzirme davranışı üzerine etkisinin belirlenmesi amacıyla tanımlayıcı ve prospektif olarak gerçekleştirilmiştir. Veriler, Süleymaniye Doğum ve Kadın Hastalıkları Eğitim Araştırma Hastanesi‟nin doğum servisinde doğum yapan ve yenidoğan servisinde yatan bebeği olan, araştırma kriterlerine uyan toplam 133 kadından toplanmıştır. Yenidoğanın sağlık durumu gözönüne alınarak iki grup oluşturulmuş ilk grupta sağlıklı yenidoğana sahip 65 ve ikinci grupta erken dönem yenidoğan sağlık sorunları olan yenidoğana sahip 68 kadın çalışmaya alınmış, veriler ilk haftada ve ilk ay sonunda toplanmıştır. Kadınların Edinburgh Postpartum Depresyon Skalası (EPDS)‟ndan aldıkları puan ortalamaları sağlıklı yenidoğan grubunda 5.86  1.90 ve sağlık sorunları olan yenidoğan grubunda 9.91 2.11 olarak saptanmıştır, Kadınların EPDS‟ndan aldıkları puan ortalamaları ve depresif belirti göstermeleri açısından gruplar arasında istatistiksel olarak anlamlı farklılık olduğu saptanmıştır (p<0.001). Sağlıklı yenidoğan grubunda kadınların %9.3‟ünde, sağlık sorunları olan yenidoğan grubunda kadınların %27.9‟unda depresif belirti saptanmıştır. Yenidoğanların, İMDAT bebeğin aldığı anne sütü miktarını puanlama sisteminden aldıkları ilk ve son ölçümlerden elde edilen puan ortalamalarında gruplar arasında istatistiksel olarak anlamlı farklılık olduğu saptanmıştır (p<0.001, p<0.01). Sağlıklı yenidoğanların ilk ölçümde %63.1‟i, ikinci ölçümde % 85.3‟ünün yetersiz anne sütü aldığı, sağlık sorunları olan yenidoğanlardan ilk ölçümde %29.2‟sinin, ikinci ölçümde %48.5‟inin yetersiz anne sütü aldığı saptanmıştır. Grup içi karşılaştırmada ilk ve ikinci ölçümlerde İMDAT puan ortalamaları her iki gruptada anlamlı saptanmıştır (p<0.001). Sağlıklı yenidoğan ve sağlık sorunları olan yenidoğan grubunda İMDAT ve EPDS puanları arasında istatistiksel olarak anlamlı bir ilişki saptanmamıştır(p>0.05). Sonuç olarak; sağlık sorunları olan yenidoğan grubundaki kadınların, sağlıklı yenidoğana sahip olan kadınlara oranla daha fazla postpartum depresif belirti gösterdiği, sağlık sorunları olan yenidoğanlarda yetersiz anne sütü alanların oranı sağlıklı yenidoğanlardan daha yüksek olarak saptanmıştır. Anne Sütü, Emzirme, Postpartum Depresyon, Yenidoğan 2.

The Effect of Newborn’s Health on Postpartum Depression and Breastfeeding Behaviors This study is conducted as supplementary to and prospective of determining the influences of the newborn‟s health on the woman under postpartum period her postpartum depression and her breastfeeding behaviors. The data were compiled from altogether 133 women who have given birth in the maternity ward of Süleymaniye Obstetrics and Gynecology Training & Research Hospital and who were conforming to the study criteria. Two groups were established among the subjects according to the newborn‟s health status. First group was consisted of 65 subjects giving birth to healthy newborns, whereas second group was consisted of 68 women giving birth to the newborns with health problems. The pertinent data were compiled in first week and at the end of month of the births. Average Edinburgh Postpartum Depression Scales (EPDS) of the women were determined as 5.86 ± 1.90 and 9.91±2.11, who had given birth to healthy and unhealthy newborns, respectively. The determination was also made for significant difference in the statistical implications of the average EPDS points and depressive symptoms of the women (p<0.001). The depressive symptoms were observed for 9.3% and 27.9% of the women who were included into the groups giving birth to healthy and unhealthy newborns, respectively. The determination was made for the significant differences in the statistical implications of the average points obtained for the quantities of the mother‟s milk taken by ĠMDAT newborn‟s points during the first and last measurements (p<0.001, p<0.01). It was also determined that 63.1% and 85.3% of the healthy newborns have taken insufficient quantities of their mothers‟ milk as measured in first and last measurements, whereas the same figures for unhealthy newborns have been 29.2% and 48.5%, respectively. Average points obtained for ĠMDAT newborns in both groups during first and last in-group measurements were also turned out to be significant (p<0.001). In both healthy and unhealthy problematic newborn groups, no statically significant relation was determined between ĠMDAT and EPDS scores (p>0.05). As a conclusion, it is established that the women included in unhealthy newborn group have undergone more postpartum depressive complications and their babies are more likely falling short in taking sufficient mother milk when compared with the group of the women who have given birth to healthy newborns. Key Words: Breast-feeding, Mother Milk, Newborn, Postpartum Depression
Keywords: Kadın Hastalıkları ve Doğum; Yenidoğan Sağlığı